Sceniczność w teatrze i tekście średniowiecznym - Bering, Piotr (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The present paper deals with different forms of staging, which are found in dramatic medieval forms and in narrative texts. As well in the theatre as in the text instructions for staging help to understand a sender’s message.
Staging in the medieval theatre and text
Keywords: Theatre; Chronicle; Staging; Narration